Evaluating the climatic suitability of Engytatus passionarius Minghetti et al. (Heteroptera, Miridae) as a biological control agent of the invasive stinking passion flower Passiflora foetida L. in Australia through ecological niche models - Eugenia Minghetti; Pablo M. Dellapé; Mariano Maestro; Sara I. Montemayor (Biological Control)
Passiflora foetida is a climbing vine, native to the Neotropical Region that is causing major economic and ecological damage in Australia, where it is rapidly spreading. Traditional control options, such as cutting, manual uprooting, and herbicide applications are only effective for local management. Currently, the plant bug Engytatus passionarius is the most promising biological control agent. Specificity tests performed in its native range in Argentina suggest it is highly specific to the plant, and it has not been observed in the field associated with other plants. As climate determines the establishment of insects, knowing if the environmental conditions suit their requirements is key to introducing a species in a region. Also, an overlap between the climatic niches of species is an indicator of similar requirements. To explore the possibilities of a successful establishment of E. passionarius in Australia, ecological niche models (ENM) were built for the plant bug and for the vine and their overlap was measured. The ENM projected to Australia recognized suitable environmental conditions for the establishment of E. passionarius in several regions where P. foetida is present, both for current and future scenarios. Moreover, the niche of the plant bug is almost completely overlapped with that of the vine. All the aforementioned evidence seems to indicate that E. passionarius has a good chance to become an effective biological control agent of P. foetida.